2021
DOI: 10.1136/openhrt-2021-001832
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of age, atherosclerosis and angiographic stenosis using artificial intelligence

Abstract: ObjectiveThe study evaluates the relationship of coronary stenosis, atherosclerotic plaque characteristics (APCs) and age using artificial intelligence enabled quantitative coronary computed tomographic angiography (AI-QCT).MethodsThis is a post-hoc analysis of data from 303 subjects enrolled in the CREDENCE (Computed TomogRaphic Evaluation of Atherosclerotic Determinants of Myocardial IsChEmia) trial who were referred for invasive coronary angiography and subsequently underwent coronary computed tomographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Here the data show that patients with diabetes have similar plaque composition in obstructive and nonobstructive lesions. This aligns with the findings of a prior study on age-based plaque composition that showed that the plaque profile becomes less distinct with more varied APC composition in older patients with longstanding disease ( 37 ). It also suggests that additional components other than distinct APCs and stenosis may be responsible for ischemia-inducing lesions in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Here the data show that patients with diabetes have similar plaque composition in obstructive and nonobstructive lesions. This aligns with the findings of a prior study on age-based plaque composition that showed that the plaque profile becomes less distinct with more varied APC composition in older patients with longstanding disease ( 37 ). It also suggests that additional components other than distinct APCs and stenosis may be responsible for ischemia-inducing lesions in this population.…”
Section: Discussionsupporting
confidence: 89%
“… 9 This FDA-cleared software service utilizes a series of validated convolutional neural networks for image quality assessment, coronary segmentation and labelling, lumen wall evaluation, vessel contour determination, and plaque characterization. Prior validation of AI-QCT has been reported in multi-centre trials using expert consensus, quantitative coronary angiography, and fractional flow reserve (FFR) as previously published, 9 , 10 , 12 as well as intravascular ultrasound. 15 The algorithm first produces a centreline, lumen, and outer vessel wall contouring for every phase available and subsequently selects the optimal series for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…AI offers an innovative approach to risk assessment, early disease detection, and guidance in formulating personalized intervention strategies. AI-driven algorithms, capable of analyzing extensive datasets, become indispensable tools for predicting patient outcomes and assisting healthcare professionals in real-time decision-making during cardiovascular interventions ( 20 ).…”
Section: Precision Cardiovascular Interventions Through Artificial In...mentioning
confidence: 99%